The Role of Photobiomodulation on Dental-Derived Stem Cells in Regenerative Dentistry: A Comprehensive Systematic Review - Firoozi, Parsa; Amiri, Mohammad Amin; Soghli, Negin; Farshidfar, Nima; Hakimiha, Neda; Fekrazad, Reza (Current stem cell research & therapy, 2024)
Photobiomodulation therapy involves exposing tissues to light sources, including light-emitting diodes or low-level lasers, which results in cellular function modulation. The molecular mechanism of this treatment is revealed, demonstrating that depending on the light settings utilized, it has the potential to elicit both stimulatory and inhibitory reactions. The current systematic review aimed to evaluate the impact of photobiomodulation therapy on dental stem cells and provide an evidence-based conclusion in this regard. This systematic review was performed and reported based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) revised guidelines. PICO(S) components were employed to define the inclusion criteria. Web of Science, Scopus, Medline as well as grey literature, and google scholar were searched up to September 2021 to retrieve relevant papers. Photobiomodulation therapy showed promising effects on the proliferation, viability, and differentiation of dental stem cells. This finding was based on reviewing related articles with a low risk of bias. Despite the positive benefits of photobiomodulation therapy on dental stem cells, the current data do not provide a definitive conclusion on the best physical parameters for enhancing cell viability, proliferation, and differentiation.